CASE REPORT: PERIOPERATIVE ANESTHESIA MANAGEMENT OF ABRUPTIO PLACENTAE COMPLICATED BY HYPOVOLEMIC SHOCK AND SEVERE COAGULOPATHY - Vicktor; Mordekhai Leopold Laihad; Wahyuddin Suleman (Journal of Scientech Research and Development, 2026)
Introduction: Abruptio placentae is a critical obstetric emergency that contributes to significant maternal and perinatal morbidity and mortality worldwide. This condition often leads to massive hemorrhage, disseminated intravascular coagulation (DIC), and profound hypovolemic shock. Case Presentation: A 32-year-old female, weighing 80 kg, Body Mass Index (BMI) 36.5 kg/m², G5P4A0 at 36-37 weeks’ gestation, was referred with severe abdominal pain and dark vaginal bleeding. Upon arrival, the patient was in decompensated shock (blood pressure 74/40 mmHg, heart rate 101 bpm) with a diagnosis of abruptio placentae and Intrauterine Fetal Death (IUFD). Laboratory findings revealed anemia (hemoglobin 10.0 g/dL), severe thrombocytopenia (58,000/uL), and impaired coagulation profiles (prothrombin time 29.4 seconds, activated partial thromboplastin time 49.5 seconds). The patient underwent an emergency cesarean hysterectomy under general anesthesia with endotracheal intubation. Intraoperative blood loss reached 1,700 mL. Management strategies included aggressive fluid resuscitation, vasopressor support, and a massive transfusion protocol (packed red cells, fresh frozen plasma, and thrombocyte concentrate). Conclusion: The successful management of such cases relies on early recognition of shock, definitive airway management, and aggressive correction of coagulopathy. Synergistic coordination between the anesthetic and obstetric teams in deciding on a timely emergency hysterectomy is crucial to control the source of hemorrhage.